Maintaining Order in Religious Worship: Goffman's Perspective – A Review Article - Ziaul Haq, Mochamad; Setia, Paelani (Parahyangan Catholic University, 2024)
Sociological studies on religion have predominantly focused on macro-sociological approaches, emphasizing structural-functional aspects or conflicts. Consequently, these studies often center on religious movements or organizations and their roles in religious life, neglecting the dynamics of social interaction in everyday religious practices. Such dynamics illustrate how individuals and groups actively shape their religious experiences. However, a different perspective has been offered by Christopher M. Donnelly and Bradley R.E. Wright, who examine religion using a micro-sociological approach, specifically symbolic interactionism. Their study focuses on the dynamics of interruptions during Christian worship services and how congregants respond to such disturbances to uphold the proper conduct of worship. These responses aim to maintain a “self-image” and safeguard the church's reputation, as conceptualized by Erving Goffman. This review aims to inspire similar explorations in other religious contexts.